Application of diversion in the investigation of criminal acts in the field of traffic against children - Supusepa, Remon; Latupeirissa, Julianus Edwin; Patty, Jetty Martje; Nussy, Jennifer Ingelyne (Universitas Wiralodra, 2023)
The aim of this research is to analyze the application of diversion in restorative justice in the Juvenile Criminal Justice System. The type of research carried out is descriptive research with a normative legal research type related to the application of diversion in restorative justice in the criminal justice system. The results of the research show that the implementation of diversion in restorative justice in the system of implementing diversion for children who are in conflict with the law in the juvenile justice system, is the implementation of a system in restorative justice to provide justice and legal protection to children who are in conflict with the law without ignoring the child's criminal responsibility. Diversion is not a peaceful effort between children in conflict with the law and their victims or families, but rather a form of punishment for children in conflict with the law in an informal way. The recommendation in this research is that law enforcement officers, in carrying out their duties of investigation, prosecution, examination and determining case decisions at court hearings, should prioritize the application of diversion as an alternative to the application of imprisonment. There needs to be massive outreach regarding diversion to the community. The government should provide diversion facilities and infrastructure in order to guarantee protection for children.